Foreign Guests in ÚMPE (Czech Journal of International Relations, 1967)
On March 20, the UMPE staff welcomed a prominent figure in American science, Prof. Karl Deutsche from Yale University in New Haven (Connecticut). Prof. Deutsch opened the friendly discussion with a short lecture on the topic of American response to the challenge of Europe. The debate deviated somewhat from its own topic, because the audience was most interested in the speaker's engaging conclusions about the use of quantitative methods in the scientific study of international relations. Prof. Deutsch, who - originally from Bohemia - gave a lecture in Czech, gave a number of examples where he achieved remarkable results with the help of these methods and using a high-speed computer.The leading representative of the Republican Party, the former vice-president of the USA and later presidential candidate Richard Nixon visited UMPE on March 23; in a short speech he answered questions from cs. of scientific workers, which mostly concerned US foreign policy, including 1 American intervention in Vietnam. Nixon, who emphasized right from the start that he was a representative of the opposition and that he had certain reservations about the foreign policy of the current US government, responded, however, in a more straightforward manner with official American positions: he warned in advance that he did not intend to criticize the government abroad. In an interesting debate, no consensus was reached on any issue of practical US policy.